THE ENCEPHALOMYOCARDITIS VIRUS (EMCV) AND ITS ZOONOTIC POTENTIAL (A LITERATURE REVIEW). PART II. PATHOGENESIS. THE CIRCLE OF SUSCEPTIBLE ORGANISMS - Akop A. Kalajdzhjan; Azamat Kh. Kade; Pavel P. Polyakov; Alla I. Gudmanova (Кубанский научный медицинский вестник, 2019)
According to literature data, both the direct action of (B2 *, L, 2A) viral proteins and the inﬂammatory response of the body are distinguished among the Encephalomyocarditis virus (EMCV) virulence factors. Depending on the EMCV strain and the type of the infected animal, the severity and nature of the disease is shown to be characterized by specific clinical manifestations. Differences in the pathogenetic mechanisms of tissue lesions depending on the magnitude of the virus infectious dose are established, e.g., in the development of EMCV-induced diabetes. The EMCV action was studied in vivo on such experimental animals as pigs, rodents and monkeys. The range of affected animals is extremely wide, with the infection being common almost everywhere. Thus, numerous works describe a fairly high immunological stratum among people, as well as disease outbreaks among the population. It is concluded that EMCV is dangerous not only for zoos and primatological centres, but also has a clear zoonotic potential.